Front row, f.l.t.r.: Schlesier, Taikeff, Juruna, Ribeiro, Jaulin, ?. On the second row on the right: Nauta - Driessen, Micha,
Front row, f.l.t.r.: Schlesier, Taikeff, Juruna, Ribeiro, Jaulin, ?. On the second row on the right: Nauta.